Purinergic Regulation of Neutrophil Function - Wang, Xu; Chen, Deyu (Frontiers in Immunology, 2018)
Purinergic signaling, which utilizes nucleotides (particularly ATP) and adenosine as transmitter molecules, plays an essential role in immune system. In the extracellular compartment, ATP predominantly functions as a pro-inflammatory molecule through activation of P2 receptors, whereas adenosine mostly functions as an anti-inflammatory molecule through activation of P1 receptors. Neutrophils are the most abundant immune cells in circulation and have emerged as an important component in orchestrating a complex series of events during inflammation. However, because of the destructive nature of neutrophil-derived inflammatory agents, neutrophil activation is fine-tuned, and purinergic signaling is intimately involved in this process. Indeed, shifting the balance between P2 and P1 signaling is critical for neutrophils to appropriately exert their immunologic activity. Here, we review the role of purinergic signaling in regulating neutrophil function, and discuss the potential of targeting purinergic signaling for the treatment of neutrophil-associated infectious and inflammatory diseases.